The Einstein almanac - Calaprice, Alice (Baltimore, Md. : Johns Hopkins University Press, 2005)
Presents an analysis of three hundred of Albert Einstein's most important publications during his lifetime, discussing his scientific and humanitarian writings, his travels, work with other scientists, and more.
A brief Einstein timeline for the years 1879-1900 -- Selected published papers & commentary, 1901-1955.
Includes bibliographical references (p. 165-168) and index.
Adult
Keywords: Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955 -- Bibliography; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955 -- Bibliography; Physicists -- Biography; Physics -- History -- 20th century; Relativity (Physics) -- History; Physicists -- Biography; Physics -- History; Relativity (Physics) -- History